Risk attitudes, job mobility and subsequent wage growth during the early career - Argaw, Bethlehem A.; Maier, Michael F.; Skriabikova, Olga J. (Mannheim, 2017)
"Job change is a decision under uncertainty: It is associated with costs whereas the decision is made without full knowledge about future benefits. In order to investigate the relationship between willingness to take risks and job mobility, we first extend a model for on-the-job search with nonwage job characteristics by including heterogeneity in risk attitudes. Second, we empirically test the model's implications showing that individuals who are more risk-averse choose to change their jobs less often than more risk-tolerant individuals. This difference in the job changing behaviour leads to only moderate differences wage growth during early career: Risk-averse individuals tend to have on average higher wage gains from each job change and have obtained higher overall wage growth at the end of the early career phase."